Structural Characterization, Optical Absorption and Electrical Conduction in Ordered Defect Compound Cu3in5se9 of the Ternary Cu-In-Se Semiconductor System - Singh, D; Enríquez-Montenegro, J (Springer, 2020)
The optical absorption coefficient α and electrical conduction as a function of temperature of the semiconductor Cu3In5Se9, an ordered defect compound which crystallizes in a tetragonal structure with space group P4 ¯ 2c, have been studied. The band gap energy EG varies between 0.994 eV and 0.983 eV in the temperature range between 25 and 300 K. The exponential variation of α with photon energy, observed just below the fundamental absorption edge, confirms the existence in Cu3In5Se9 of the Urbach’s tail. The phonon energy hνp associated with this tail is 101 meV. This is about three times higher than the highest optical phonon mode reported for Cu3In5Se9 from infrared reflectivity spectra. The origin of this high energy is attributed due to the contribution of localized modes produced by structural disorders due to deviation from ideal stoichiometry and donor–acceptor defects pairs. From the analysis of electrical data of n-type Cu3In5Se9 in the temperature range from 80 K to 300 K, it was found that above 100 K the electrical conduction is due to the activation of two shallow donor levels of about 40 meV and 80 meV, probably due to selenium vacancies. © 2019, The Minerals, Metals & Materials Society.
Keywords: Ordered defect semiconductors; band-to-band transition; Urbach s tails; electrical conduction; crystal structure characterization